Analisis Pengaruh Islamic Corporate Governance terhadap Manajemen Laba pada Bank Umum Syariah di Indonesia dan Malaysia - Amirul Arif; Agus Purwanto (Faculty of Economics and Business, University of Pancasakti Tegal, 2020)
The objective of the research is to analyze the effect of Islamic Corporate Governance toward the earnings management of Islamic banks in Indonesia and Malaysia. In South East Asia region, Malaysia and Indonesia are two countries with significant development in Islamic banking and finance. Islamic Banks have different characteristics from conventional banks, however they still deal with the financing risk that could not be claimed, so it is necessary for them to have loan loss provision that lead to the existence of earnings management. The populations of the research are some Islamic Banks located in Indonesia and Malaysia during the period of time 2012 until 2017. The total amount of samples in the research is 108. After conducting the tabulation of data stage, there is no outlier data, so that the amount of final samples remains 108. This research used data panel regression, Fixed Effect model. The result of the research showed that the meeting of Islamic supervisory council, audit committee's independence and the meeting of audit committee have significant effect toward the earnings management, meanwhile the number of Islamic supervisory council and audit committee do not have significant effect on the earnings management.